2019
DOI: 10.22207/jpam.13.2.43
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pH Dependent Growth Response of Agriculturally Important Microbes for Development of Plant Growth Promoting Bacterial Consortium

Abstract: Soil microbial community structure is influenced by both biotic and abiotic factors prevailing in the soil milieu. The pH is one of the noticeable abiotic factors that affect soil microbial community. Different species prefer different range of pH for their optimal growth; however they can tolerate a wide range around acidic, neutral or alkaline pH. Microbes with broad range of pH tolerance i.e. from acidic to alkaline soil have better survival rate or opportunity as compared to other microbes which have narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…9,10 These three isolates were also tolerant and grew in a broad pH range (pH 3.5-10). 10 These three isolates were used in this study.…”
Section: Materials and Methods Source And Information Of The Microbia...mentioning
confidence: 98%
See 2 more Smart Citations
“…9,10 These three isolates were also tolerant and grew in a broad pH range (pH 3.5-10). 10 These three isolates were used in this study.…”
Section: Materials and Methods Source And Information Of The Microbia...mentioning
confidence: 98%
“…Three bacterial isolates (E-2, T-2, and T-1) were obtained from Kumar's laboratory at Central University of Jharkhand, India. 9,10 All three isolates exhibited four plant growth-promoting characteristics: (1) nitrogen fixation, (2) phosphate solubilization, (3) siderophore production, and (4) Indole acetic acid production. 9,10 These three isolates were also tolerant and grew in a broad pH range (pH 3.5-10).…”
Section: Materials and Methods Source And Information Of The Microbia...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the results it can be observed that the pH of the soil was slightly acidic which is suitable for the growth of the most of plants (Kumar et al 2019). In addition, some useful microorganisms can tolerate acidic pH and are applicable for crop enhancement (Kumar et al 2019). Soil is the largest deposit of heavy metals such as arsenic and their compounds.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of arsenic in the drinking water of the Terai region has been a long-standing public health issue of Nepal [ 40 ]. The soil profile of processed samples in this study reveals a slightly acidic pH (5-6); while soil microbes exhibit tolerance to a wide range of pH (3–13) [ 41 ]. Among 158 isolates of Bacillus species, five isolates N 4-1, RW, KR7-12, Bhw 4-1, and BW2-2 were found to be arsenic tolerant in culture media and could grow on NB containing a sodium arsenite concentration of >600 ppm.…”
Section: Discussionmentioning
confidence: 99%